OPTIMIZING EMBRYONIC DEVELOPMENT, EGG HATCHABILITY, AND LARVAL SURVIVAL OF ASIAN SEABASS, Lates calcarifer USING PAPAYA LEAF EXTRACT (Carica papaya) TREATMENTS - Teuku Fadlon Haser; Fauziah Azmi; Muh Saleh Nurdin; Suri Purnama Febri; Tri Heru Prihadi; Joel Aubin; Bahtiar Sah Putra; Riris Yuli Valentine; Deni Radona; Kurniawan Kurniawan; Muhammad Haritza Laitte (Indonesian Aquaculture Journal, 2022)
Embryonic development of Asian seabass, Lates calcarifer is a critical phase in the success of larval rearing production in a hatchery. Low production of larvae has been the drawback of the Asian seabass aquaculture owing to diseases and microbial infection to the eggs, causing low egg viability. This study aims to evaluate the effect of different doses of papaya leaf extracts during embryonic development to improve egg hatchability and larval survival. Six different doses of papaya leaf extracts of 2, 4, 6, 10, 20, and 25 mL were used as treatments arranged triplicates in five liter aquaria. The newly fertilized eggs (99 eggs) were immersed in each treatment for five minutes and fifteen seconds. Subsequently, the eggs were moved into 10 L incubation tanks, and samples were collected for embryogenesis observation. The hatchability of eggs was significantly different among treatments. The hatchability of larvae in group with dose of 4 mL was the best treatment (93.94 ± 0.1%) followed by 2 mL (93.88 ± 3%), and 6 mL (90.91 ± 3.0%). The different doses of papaya leaf extract significantly affected larval survival. The highest survival rate of larvae was 2 mL (93%) followed by 4 mL (90%) and 6 mL (70%). There was no significant difference in the hatching time of larvae. The fastest hatching time occurred at the dose of 6 mL about 13 hours and 30 minutes, followed by 2 mL and 4 mL treatment for about 14 hours. This study recommends that the doses of 2 mL or 4 mL of papaya leaf extracts have potential impacts on the improvement of larval rearing production for Asian seabass hatchery.